Pembentukan Peradilan Agraria sebagai Instrumen Hukum Administrasi Negara dalam Penyelesaian Konflik HGU Perkebunan - Edward Benedictus Roring; Zul Amirul Haq; Salman Alfarisi (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to examine the sociological conditions of the HGU conflict, and to analyze the need for the establishment of an Agrarian Court from a legal and social aspect. The method used in this study is the Sociolegal method, which combines law with social reality. Primary data was taken from interviews with farmers, residents affected by HGU, BPN officials, Secondary data was obtained from laws and regulations, court decisions, NGO reports, land documents. Mesuji Regency is an area in Lampung Province which is known as one of the chronic agrarian conflict areas in Indonesia, especially those involving the Right to Cultivate (HGU) by large plantation companies including PT Barat Selatan Makmur Investindo (BSMI) and PT Silva Inhutani. This conflict involves local communities and companies holding HGU. The root of the problem is the community's claim to customary land, cultivated land, or inherited land. Allegations of HGU expansion that exceed the permit limit. The conclusion of this study is that the resolution process is often ineffective, unfair, and slow. HGU conflicts are generally structural in nature, because they involve inequality between local communities and large corporations that receive legal legitimacy through the granting of HGU. The establishment of an Agrarian Court has the potential to be a more just, effective, and contextual solution to resolving plantation HGU conflicts.